2007
DOI: 10.1002/dneu.20399
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen mediation of injury‐induced cell birth in neuroproliferative regions of the adult zebra finch brain

Abstract: Estrogens influence neuronal differentiation, migration, and survival in intact brains. In injured brains, estrogens can also be neuroprotective. In Experiment 1, following a unilateral penetrating injury to the hippocampus (HP), adult female zebra finches were injected once with BrdU to label mitotic cells then sacrificed 2 h, 1 day, or 7 days postinjection. Cell proliferation was dramatically enhanced in the ipsilateral HP, as well as in neuroproliferative areas including the subventricular zone (SVZ) proxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 47 publications
3
37
1
Order By: Relevance
“…Given previous studies establishing the involvement of the oestrogen receptors ERa, ERb and GPER-1 in neuroprotection following brain injury (15,16,(18)(19)(20)(22)(23)(24)(25)(26)(27), we were surprised to find no differences in the expression of these receptors in the present experiment. We did, however, observe a significant down-regulation of AR expression in the injured hemisphere compared to the uninjured hemisphere of both male and female zebra finches (Fig.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Given previous studies establishing the involvement of the oestrogen receptors ERa, ERb and GPER-1 in neuroprotection following brain injury (15,16,(18)(19)(20)(22)(23)(24)(25)(26)(27), we were surprised to find no differences in the expression of these receptors in the present experiment. We did, however, observe a significant down-regulation of AR expression in the injured hemisphere compared to the uninjured hemisphere of both male and female zebra finches (Fig.…”
Section: Discussioncontrasting
confidence: 48%
“…Similarly, administration of peripheral E 2 attenuates the increased neuronal damage induced by aromatase inhibition following injury in mice (17). In addition to the mitigation of neuronal damage and secondary degeneration following brain injury, E 2 has also been suggested to enhance neurogenesis after injury (18)(19)(20). The data strongly suggest that the neuroprotective effects of centrally synthesised E 2 are a conserved characteristic across several vertebrates.…”
mentioning
confidence: 86%
“…Therefore, it is likely that environmental enrichment and physical exercise together may increase cognitive ability in male Ts65Dn mice, which otherwise exhibit deteriorated cognitive function under standard enriched environment [34]. The distinctive early effect of enrichment and wheel running on female Ts65Dn SVZ proliferation and neurogenesis suggests a potential role of sex hormones such as estrogen on these cellular changes [54,55]. In fact, in animal models of brain injury, it has been shown that there is a gender-based difference in the response of SVZ cells on proliferation after the injury [56].…”
Section: Discussionmentioning
confidence: 99%
“…Relative to other aromatase inhibitors, LET has been employed to only a limited extent in songbirds, and although we found clear evidence of its efficacy, the drug was not tolerated well in zebra finches at doses comparable to an orally administered aromatase inhibitor in a previous study [46]. However, LET appears to be more effective than another popular aromatase inhibitor, ATD, at least under certain experimental conditions [36,74].…”
Section: Discussionmentioning
confidence: 59%